Migrant self-selection in the presence of random shocks. evidence from the panic of 1907 - Escamilla-Guerrero, D; Lopez-Alonso, M (University of Oxford, 2020)
We evaluate the responsiveness of migrant self-selection to short-run changes in the economic environment. Using novel historical micro data, we estimate the initial selectivity of Mexican migration (1906-08) and focus on labor institutions as short-run adjustment channels of self-selection. We find that the first Mexican migrants were positively self-selected on the basis of height—a proxy for physical productivity of labor. Additionally, the US financial crisis of 1907 significantly modified self-selection. Shifts in migrant self-selection during and after the crisis were influenced by the enganche, an institution that reduced migration costs, but only for the "best" Mexicans during "good" economic times.